Notch Signaling in Acquired Middle Ear Cholesteatoma. Issue 9 (October 2021) - Fukuda, Atsushi; Kano, Satoshi; Nakamaru, Yuji; Morita, Shinya; Hoshino, Kimiko; Fujiwara, Keishi; Homma, Akihiro
Abstract : Hypothesis: We hypothesized that an anomalous change of Notch signaling might be involved in the pathophysiology of cholesteatoma. Background: The Notch signaling pathway regulates integrated growth and differentiation control of keratinocytes. Its involvement in cholesteatoma proliferation has not been elucidated. Methods: We obtained cholesteatoma and external auditory canal (EAC) skin samples from patients with middle ear cholesteatoma who underwent tympanomastoid surgery. We performed polymerase chain reaction using the RT 2 Profiler™ PCR Array Human Notch Signaling Pathway (Qiagen) in the cholesteatoma and EAC skin samples (n = 6 each). This was followed by immunohistochemical staining of Notch1, enhancer of split-1 (HES1), and p53 in 41 and 8 cholesteatoma and EAC skin samples, respectively. Results: The fold change of Notch1 gene expression was lowest in cholesteatoma, with a statistically significant difference ( p  = 0.0424). Moreover, the fold change of HES1 expression decreased ( p  = 0.272). The positive rates of Notch1 and HES1 protein expressions in the cholesteatoma (48.5 ± 32.4% and 44.9 ± 17.8%, respectively) were significantly lower than in the EAC skin (83.4 ± 17.5% and 55.7 ± 7.1%, respectively) ( p  < 0.001 and p  < 0.01). In contrast, the positive rate of p53 expression in the cholesteatoma (8.5 ± 11.4%) was significantly higher than in the EAC skin (0.5 ± 0.7%) ( p  < 0.001). Conclusion: The decreases in Notch1 and HES1 protein expression might play an important role in the hyperproliferative character of the keratinizing squamous epithelium in cholesteatoma. An increase in p53 might reflect the reaction to cellular hyperproliferation.